Evaluation of α‐synuclein as a novel cerebrospinal fluid biomarker in different forms of prion diseases. Issue 6 (18th November 2016) - Llorens, Franc; Kruse, Niels; Schmitz, Matthias; Gotzmann, Nadine; Golanska, Ewa; Thüne, Katrin; Zejneli, Orgeta; Kanata, Eirini; Knipper, Tobias; Cramm, Maria; Lange, Peter; Zafar, Saima; et al.
Abstract: Introduction: Accurate diagnosis of prion diseases and discrimination from alternative dementias gain importance in the clinical routine, but partial overlap in cerebrospinal fluid (CSF) biomarkers impedes absolute discrimination in the differential diagnostic context. Methods: We established the clinical parameters for prion disease diagnosis for the quantification of CSF α‐synuclein in patients with sporadic ( n  = 234) and genetic ( n  = 56) prion diseases, in cases with cognitive impairment/dementia or neurodegenerative disease ( n = 278), and in the neurologic control group ( n = 111). Results: An optimal cutoff value of 680 pg/mL α‐synuclein results in 94% sensitivity and 96% specificity when diagnosing sporadic Creutzfeldt‐Jakob disease (CJD). Genetic CJD cases showed increased CSF α‐synuclein values. No increased α‐synuclein levels were detected in non‐CJD cases with rapid progression course. Discussion: Detection of α‐synuclein in the CSF of patients with suspected CJD is a valuable diagnostic test reaching almost full discrimination from non‐prion disease cases. These data highlight the utility of CSF α‐synuclein quantification in front of classical CSF biomarkers in clinical routine.